Antifungal and biodegradable nanoencapsulation of Smallanthus Sonchifolius essential oil for improved stability and sustained release - Wang, Jiajie; Wang, Fei; Zhang, Yu; Li, Xun (Frontiers in Microbiology, 2025)
IntroductionPhytopathogenic fungi pose a serious threat to global crop productivity, necessitating sustainable alternatives to chemical fungicides.MethodsThis study developed poly-ε-caprolactone (PCL) nanospheres encapsulating essential oil extracted from Smallanthus sonchifolius tubers (SsEO) to enhance antifungal stability and efficacy.ResultsThe nanospheres exhibited a high encapsulation efficiency of 98%, significantly improved the photostability of SsEO by protecting it from UV-induced degradation, and provided a sustained-release profile that extended its functional longevity. In vitro assays showed that the nanoencapsulated SsEO inhibited Sclerotinia sclerotiorum and Valsa mali by 93.6% and 56.9%, respectively, while in vivo inhibition rates reached 94.45% and 92.5%.ConclusionThese findings demonstrate that biodegradable, photoprotective PCL nanospheres offer a promising eco-friendly strategy for plant pathogen management, reducing reliance on chemical fungicides, and minimizing environmental impact.environmental impact.